PRESENCE OF SUMATRAN ELEPHANTS (Elephas maximus sumatranus) IN THE ECOTONE AREA OF SEMBILANG NATIONAL PARK (TNSTNS) AND PALM OIL PLANTATION IN SEMENANJUNG BANYUASIN SEMENANJUNG, SOUTH SUMATRA PROVINCE - Pirnanda, Dafid; Yustian, Indra; Dahlan, Zulkifli; Indrianti, Winda; Aprilia, Ina; Ridwan, Alex; Setiono, Setiono; Travolindra, Yoga; Deviani Salaki, Larissa (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
A research to monitor the presence of Sumatran elephant between two ecosystem in Sembilang National Park (TNSTNS) and palm palm oilplantation has been conducted on March until June 2019 at Semenanjung Banyuasin Semenanjung, South Sumatra. This research aimed to verify the presence of Sumatran elephantpopulation and to estimate the number of elephant individuals in the area. The methods used weredirect observation during the day and indirect monitoring through installation of Camera Traps for 1 month. In addition, secondary data was collected in the form of data archives from the palm oil plantation records and interviews with affected plantation workers. From direct observation, Wedirect encountered one elephant individual and fifteen signs of elephant activities, such as sounds, footprints, and feces. From camera trap photos, we identified and verified onepopulation of Sumatran Elephants which consisted of at least twenty-two individuals with composition as follows: eight adult females, two young females, three infant females, and nine males. The ecotone area between TNS and palm palm oil plantation should be designated as a new habitat patchof Sumatran elephant that needs to be managed appropriately in order to maintain the designation of the area as aÂ conservation area.